Use of a Psychometric Instrument as a Referral Process for the Required Level of Specialization of Health and Social Services. Issue 1 (6th February 2015) - Tremblay, Audrée; Morin, Diane
Abstract In Québec, services of people with intellectual disability (ID) are divided into three levels of care based on the World Health Organization model. Currently, no standardized tool is used to assess the level of specialization of care required by persons with ID in the province despite the Ministry of Social and Health Services' reference framework, which stipulates that services should be fair and easily accessible to all. The present study examined potential tools to address this situation. The scores on the Supports Intensity Scale‐French version (SIS‐F), Adaptive Behavior Assessment System‐II, and Scales of Independent Behavior‐Revised (SIB‐R) (Part 2) of 30 participants with ID were examined in conjunction with the required level of specialization of services, as determined by an expert committee. Scores on these scales were not linearly related to the required level of care. This indicates that scores cannot be used to determine if a person needs services from the primary, secondary, or tertiary care facility. However, significant differences were observed between the primary and tertiary levels on the Exceptional Behavioral Support Needs scale of the SIS‐F and the SIB‐R Part 2. The study shows that the expert committee was more successful in making this determination than a standardized instrument. The instruments used in the present study, not designed for this purpose, were insufficient. Nonetheless, results underline the importance of factoring in challenging behaviors in the assessment of service needs.